INTERAKSI YANG DISUKAI MAHASISWA YANG PERNAH DIALAMI DALAM LINGKUNGAN KAMPUS - Sudarto Sudarto; Sri Indriyani (Sekolah Tinggi Pariwisata Mataram, 2023)
This research is a survey research that aimed to find out the forms of interaction that students like that they have experienced since entering in Universitas Negeri Makassar (Campus VI Bone) until May 2023. The subjects of this study were Elementary School Teacher Education Students, Campus VI UNM Bone, in totaling 30 people. Data collection using a questionnaire. As for the data source here, there were 30 meetings counted when students entered college. Research results and conclusions: the forms of interaction that students like since entering in Universitas Negeri Makassar were: Interaction with Lecturers in class when discussing lecture material, Interaction with Academic Advisor Lecturers regarding academic issues, Interaction with Campus Operators regarding administration , Interaction with Head of Level regarding course schedules, Interaction with Lecturers regarding implementation of workshops/seminars, Interaction between students in ASCOM activities (competition), Interaction with fellow students in coordination meetings attended by all campus organizations, Interaction with Lecturers regarding exhibitions carried out in the campus hall, Interaction with co-heads and staff in committee meetings (cooperation), Interaction with fellow students in deliberation forums, Interaction with Campus Security, Interaction with Assembly in Science meetings, Interaction with group mates in completing a project, Interaction in determining the level head in the class, Interaction in determining the level head in the class, and Interaction with Lecturers regarding the project or assignment given